MENINGKATKAN PROFESIONALISME GURU MELALUI PENERAPAN SUPERVISI PENDIDIKAN DI SDN 004 TELUK BINJAI - Iskandar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article examines the improvement of teacher professionalism through the implementation of educational supervision. Professional teachers are expected to facilitate students in optimizing their potential to achieve maximum learning outcomes. Educational supervision is a structured effort aimed at improving, adapting, and developing educators’ competencies individually or in groups sustainably. It is often interpreted as enhancing the quality of students’ learning outcomes and processes through professional guidance by school supervisors. The research used School Action Research (SAR) with the Kemmis and McTaggart design model and was conducted at SDN 004 Teluk Binjai. The study involved 24 teachers as subjects. Two cycles of supervision were carried out, showing an increase in teacher competence. The pre-cycle assessment indicated an average competence score of 66.66, categorized as “quite sufficient.” Cycle I yielded 70.83, still “quite sufficient,” and Cycle II achieved 87.50, categorized as “good.” These results demonstrate that educational supervision effectively improves teacher professionalism.